CONVENTION REPORT. (The Accounting Review, 1931)
Abstract The article presents a report on the fifteenth annual convention of the American Association of University Instructors in Accounting, held in hotel Cleveland on December 29 and 30, 1980. President A.H. Rosenkampff presided over the sessions. The annual dinner of the association held on Monday, December 29, at 7:15 P.M. At the close of the dinner, President Rosenkampff called for reports of committees. The Classification of Accountancy services as presented by the American Society's Committee, may be worked out for students who are preparing to enter the professional field of accountancy. The Committee on Research sent out, under date of August 19 1980, to the entire membership, a Questionnaire on the Treatment of Appreciation. The content of the report of Membership Committee was divided into, Organization of the Committee, Plan of Operation, Results and Conclusions. The plan of procedure followed by the committee seems to hold much promise.